The Development of e-Learning to Enhance Learning Achievement on Technology (Computing Science) Using 5 STEPs Learning Process for Mathayomsuksa 1 Students (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purposes of this research study were: 1) to develop e-Learning to enhance learning achievement on Technology (Computing Science) using 5 STEPs learning process for Mathayomsuksa 1 students 2) to find the efficiency of e-Learning 3) to compare pretest and posttest score, and 4) to study students’ satisfaction. The sample in this research study consisted of 30 students in Mathayomsuksa 1 of Krabyai Vongkusolkit Phitthaykhom school. The simple random sampling method was used. The research instruments included e-Learning, quality of content evaluation form, quality of production techniques evaluation form, quality of lesson plans evaluation form, learning achievement test, and satisfaction questionnaire. Data were analyzed using mean , standard deviation (S.D.) and dependent t-test. The research results were as follows: 1) e-Learning was comprised of two parts: 1.1) Data and Information Management and 1.2) Using Technology Safely. 2) The efficiency of e-Learning to enhance learning achievement on Technology (Computing Science) using 5 STEPs learning process was 83.58/80.50, that higher than the standard criteria (80/80), 3) the posttest score was significantly higher than the pretest score at .05 level, and 4) students were satisfied after learning by e-Learning to enhance learning achievement on Technology (Computing Science) using 5 STEPs learning process at highest level (Mean = 4.90, S.D.= 0.31).